Delivering benefit : technical leadership capabilities - Sutton, Brian (Systems management professor); Chatham, Robina (BCS Learning and Development, 2017)
The development of technical leadership capabilities is often overlooked as a training requirement in organisations but skills such as thinking strategically and recognising opportunities are key to business success. In this book, management experts Brian Sutton and Robina Chatham describe and explain six management techniques to help you develop your leadership capabilities and deliver benefit to your customers, team and organisation. With real life examples, tips and mini exercises, you'll also boost your soft skills as you improve your professional value. ''A highly valuable resource based upon sound management principles, with comprehensive and pertinent explanations. Great advice for those at all levels of leadership within the technology sector.'' A.P. Sutcliffe, MSc CCI, MBCS -- ''A very practical and usable guide to improving your working environment, increasing the value of your contribution and enhancing the quality of the legacy you leave behind.'' Tanya Foster-Fitzgerald FBCS, Raytheon, CIO.